Changing in place? Neighbourhood change and place attachment among movers and stayers in Los Angeles. Issue 5 (27th September 2018) - Sharp, Gregory
Abstract: Recent research on neighbourhood effects has stressed the importance of adopting a dynamic approach by incorporating residential mobility into analyses of neighbourhood change and individual outcomes. This study uses longitudinal data from the Los Angeles Family and Neighbourhood Survey to examine how changes in residential neighbourhood conditions shape two dimensions of place attachment—neighbourhood satisfaction and neighbouring—for people who leave the neighbourhood and for residents who remain in place. Results from fixed‐effects regression models present a nuanced picture of the ways in which changing neighbourhoods intersected with residential mobility shape individuals' attachments to place. Stayers tend to become less satisfied when their neighbourhoods are becoming more disadvantaged and diverse but also when they become more residentially stable, whereas movers are more satisfied when relocating to neighbourhoods with higher levels of ethnoracial diversity. Moreover, neighbourhood fear and victimisation reduce satisfaction for both movers and stayers, but stayers' neighbouring declines in response to heightened fear whereas movers neighbour less when victimised. These findings suggest that investigations of the effects of neighbourhood change on place attachment should examine movers and stayers separately to account for differential neighbourhood selection processes.